Transition to ustekinumab in patients with moderate‐to‐severe psoriasis and inadequate response to methotrexate: a randomized clinical trial (TRANSIT). (1st February 2014) - Paul, C.; Puig, L.; Kragballe, K.; Luger, T.; Lambert, J.; Chimenti, S.; Girolomoni, G.; Nicolas, J.‐F.; Rizova, E.; Lavie, F.; Mistry, S.; Bergmans, P.; et al.
Summary: Background: Limited data exist on transitioning patients with psoriasis from conventional systemic agents to biologics. Objectives: The TRANSIT study aimed to assess the efficacy and safety of two methotrexate‐to‐ustekinumab transition strategies. Methods: Patients with moderate‐to‐severe psoriasis and inadequate methotrexate response were randomized 1 : 1 to receive ustekinumab with immediate (arm 1) or 4‐week gradual (arm 2) methotrexate withdrawal. Patients weighing ≤ 100 kg or > 100 kg received ustekinumab 45 mg or 90 mg, respectively. The primary endpoint was the frequency of adverse events (AEs) at week 12. Secondary endpoints included additional safety, efficacy and patient‐reported outcomes. We report the 12‐week efficacy and safety results. Results: Overall, 244 patients in arm 1 and 245 in arm 2 were randomized and received ustekinumab. Four patients per arm discontinued the trial by week 12. At week 12 in arms 1 and 2, respectively, 61% and 65% of patients experienced an AE, 2·9% and 2·4% had a serious AE, and 1·2% and 0·4% had an AE leading to ustekinumab discontinuation. In arms 1 and 2, respectively, median Psoriasis Area and Severity Index (PASI) score decreased from 15·2 and 15·4 at baseline to 2·9 and 2·8 at week 12; 58% and 62% of patients achieved a 75% reduction from baseline in PASI score (PASI 75) at week 12; median baseline Dermatology Life Quality Index fell from 8 and 9 at baseline to 1 (both arms) at week 16. Conclusions: Ustekinumab was well tolerated and effective in patients who had an inadequate response to methotrexate. Both transition strategies resulted in similar week 12 safety and efficacy outcomes.